2022
DOI: 10.1002/poi3.285
|View full text |Cite
|
Sign up to set email alerts
|

Consumer IoT and its under‐regulation: Findings from an Australian study

Abstract: The expansive growth of consumer internet of things (IoT) has created a range of concerns around privacy, security, and their broader societal impacts. This article reports on findings from interviews with 32 key stakeholders from the fields of information security, policy and regulation, the IoT industry, consumer and privacy law, and academia in Australia. It details a broad variety of issues and concerns that go beyond the well-recognised issue of privacy or the technical standards of information security, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…When assessing the security regulations of personal IoT devices from an Australian perspective, it has previously been identified that the regulation of IoT in Australia could be more robust [35]. An insipid set of regulations can leave consumers vulnerable to security, privacy, and consent dangers [144].…”
Section: ) Iot Regulation In the Australian Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…When assessing the security regulations of personal IoT devices from an Australian perspective, it has previously been identified that the regulation of IoT in Australia could be more robust [35]. An insipid set of regulations can leave consumers vulnerable to security, privacy, and consent dangers [144].…”
Section: ) Iot Regulation In the Australian Contextmentioning
confidence: 99%
“…While the voluntary code of practice is a step forward, standardisation of IoT is necessary for the robust regulation of the industry. As it currently stands, standards throughout Australia address the overall electrical safety of the device and not the security and privacy aspects VOLUME 4, 2022 [35]. This, however, is changing, with recommendations from the ACCC following their 2019 inquiry paving the way for a suite of reforms that include enhanced protection for consumers under the privacy act [35].…”
Section: ) Iot Regulation In the Australian Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving beyond the digital confines of Internet applications such as TikTok and other social media platforms is the consideration of consumer IoT as a permeable force and its under‐regulation. According to Harkin et al (2021) in Consumer IoT and its under‐regulation: Findings from an Australian study , under‐regulation is not only impacting consumer privacy and security but presents ‘a wider set of issues regarding the implications for vulnerable communities, the environment, and industrial standards of IoT production’. Aligning with the emerging theme of ambiguity and legitimacy, these scholars hone in on the lack of appropriate regulation for this reasonably area of information and communication technologies.…”
Section: Reconceptualisation and Regulationmentioning
confidence: 99%